Desalination with a solar-assisted heat pump, an economic optimization - Amin, Zakaria Mohd.; Maswood, Ali. I.; Hawlader, Mohammad Nurul Alam; Al-Ammar, Essam; Orfi , Jamel; Al-Ansari, Hani (Institute of Electrical and Electronics Engineers Inc, 2013)

(untitled)
The Solar Assisted Heat Pump (SAHP) desalination, based on the Rankin cycle operates in low temperature and utilizes both solar and ambient energy. An experimental SAHP desalination system has been constructed at the National University of Singapore (NUS). The system consisted of two main sections: a solar assisted heat pump and a water distillation section. Experiments were carried out under the different metrological condition of Singapore and results showed that the system had a performance ratio close to 1.3. The heat pump has a Coefficient of Performance of about 8, with solar collector efficiencies of 80% and 60% for evaporator and liquid collectors, respectively. Economic analysis showed that at a production rate of 900 liter/day and an evaporator collector area of around 70 m2, will have a payback period of about 3.5 years.